If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + 7(3x + -4) = 179 Reorder the terms: 2x + 7(-4 + 3x) = 179 2x + (-4 * 7 + 3x * 7) = 179 2x + (-28 + 21x) = 179 Reorder the terms: -28 + 2x + 21x = 179 Combine like terms: 2x + 21x = 23x -28 + 23x = 179 Solving -28 + 23x = 179 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '28' to each side of the equation. -28 + 28 + 23x = 179 + 28 Combine like terms: -28 + 28 = 0 0 + 23x = 179 + 28 23x = 179 + 28 Combine like terms: 179 + 28 = 207 23x = 207 Divide each side by '23'. x = 9 Simplifying x = 9
| 3y+2x=62 | | x^2+5-(7+3*x)= | | 2.3*(-1.2)= | | 7-7x=34-14x | | -35+8+m=-8+11 | | 6x+2(4x+15)=198 | | -1.1*(-8)= | | -15*(-3)= | | 0.4n+-18=3n-16-0.8n | | 5x+5(2x+18)=195 | | 6x+10=-48-8x | | y+31=-55 | | 16-m^2=0 | | w^2+8w+48=0 | | 2[(3)+2]4= | | 0.4n-18=3n-16-0.9n | | a^2-10-3a= | | 6(2x-5)-3(x+2)-18x= | | 2(6-2b)=0 | | 2(3m-10)= | | 5y+2=3y-1 | | 2(3m+5)= | | 3x+6=89-5x | | -27=x+19 | | -2(5-3m)= | | 3(7)/3= | | 3z-(10)=1 | | log(12x^4)-log(2x^3)=2 | | 4(5+7b)+6b=-252 | | cos(x)=-0.5 | | 5ln(x-11)-3=7 | | 8x^2-6x-3=0 |